Biosensing strategies for the detection of SARS-CoV-2 nucleic acids - Tamborelli, Luis Alejandro (2023)
The COVID-19 pandemic had devastating effects throughout the world, producing a severe crisis in the health systems and in the economy of a long list of countries, even developed ones. Therefore, highly sensitive and selective analytical bioplatforms that allow the descentralized and fast detection of the severe acute respiratory síndrome coronavirus 2 (SARS-CoV-2), are extremely necessary. Since 2020, several reviews have been published, most of them focused on the different strategies to detect the SARS-CoV-2, either from RNA, viral proteins or host antibodies produced due to the presence of the virus. In this review, the most relevant biosensors for the detection of SARS-CoV-2 RNA are particularly addressed, with special emphasis on the discussion of the biorecognition layers and the different schemes for transducing the hybridization event.